2006
DOI: 10.1128/mcb.26.2.727-734.2006
|View full text |Cite
|
Sign up to set email alerts
|

RalB Mobilizes the Exocyst To Drive Cell Migration

Abstract: The Ras family GTPases RalA and RalB have been defined as central components of the regulatory machinery supporting tumor initiation and progression. Although it is known that Ral proteins mediate oncogenic Ras signaling and physically and functionally interact with vesicle trafficking machinery, their mechanistic contribution to oncogenic transformation is unknown. Here, we have directly evaluated the relative contribution of Ral proteins and Ral effector pathways to cell motility and directional migration. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
149
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(157 citation statements)
references
References 35 publications
(43 reference statements)
7
149
1
Order By: Relevance
“…Furthermore, essential roles for Ral have been demonstrated in cell migration (Suzuki et al, 2000;Takaya et al, 2004;Oxford et al, 2005;Rosse et al, 2006), and, more locally, in the induction of lamellipodial protrusion at the front of migrating cells (Takaya et al, 2004). We have shown that PI3K, Cdc42, and Rac play important role in such localized activation of Ral (Takaya et al, 2004).…”
Section: Introductionmentioning
confidence: 77%
“…Furthermore, essential roles for Ral have been demonstrated in cell migration (Suzuki et al, 2000;Takaya et al, 2004;Oxford et al, 2005;Rosse et al, 2006), and, more locally, in the induction of lamellipodial protrusion at the front of migrating cells (Takaya et al, 2004). We have shown that PI3K, Cdc42, and Rac play important role in such localized activation of Ral (Takaya et al, 2004).…”
Section: Introductionmentioning
confidence: 77%
“…For example, in neurons undergoing differentiation or synapse formation, the exocyst is enriched at the expanding neurites and discrete puncta along axons where synapses are forming (Hsu et al 1996;Kee et al 1997;Hazuka et al 1999;Vega and Hsu, 2001;Brown et al 2001;Murthy et al 2003). In migrating cells, the exocyst is recruited to the plasma membrane at the leading edge (Zuo et al 2006;Rosse et al 2006). During the formation of epithelial cell monolayers, the exocyst is recruited to the plasma membrane at sites of cell -cell contact (Grindstaff et al 1998), where it targets vesicles that carry proteins to the basolateral domain.…”
Section: Membrane Organization and Dynamics In Cell Polaritymentioning
confidence: 99%
“…However, they are recruited to the PM during a number of cellular processes. For example, in epithelial cells, the exocyst is recruited to the adherens junction region upon cell-cell contact, where it mediates protein and membrane addition at the basolateral domain (Grindstaff et al, 1998;Yeaman et al, 2001); in developing neurons, the exocyst is localized to the growing neurites, where it mediates membrane expansion (Hazuka et al, 1999;Vega and Hsu, 2001); during cell migration, the exocyst is recruited to the leading edges of the PM (Rosse et al, 2006;Zuo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%